Pengaruh Tekanan Waktu, Pengalaman, Kepribadian, dan Skeptisisme Profesional terhadap Kemampuan Auditor Mendeteksi Kecurangan - Nur Maulidah; Made Dudy Satyawan (Jurnal Akuntansi, 2021)
This research was conducted to find out the factors that affect the fraud detection ability of auditors, namely factors of time pressure, experience, personality, and professional auditor skepticism. Auditors who work at KAP Surabaya are the population used by purposive sampling of 60 auditors. This research is a quantitative type research with the help of multiple linear regression analysis tools with dummy variables. Primary data with the distribution of online and offline questionnaires is a type of data from research. The results showed that time pressure and professional skepticism had a significant effect on the ability to detect fraud, while the auditor experience and personality variables did not significantly influence the ability to detect fraud.